International youth mobility in Eastern and Western Europe – the case of the Erasmus+ programme - Dabasi-Halász, Zsuzsanna; Kiss, Julianna; Manafi, Ioana; Marinescu, Daniela Elena; Lipták, Katalin; Roman, Monica; Lorenzo-Rodriguez, Javier (Migration Letters, 2018)
A country’s mobility pattern is largely influenced by its previous historical development and current socio-economic situation. Hungary and Romania, due partly to the legacy of their socialist past, share many of their social and economic characteristics, which differ from countries in Western Europe. Such differences are also present when looking at the issue of international youth mobility, which contrast not only by rate but also by type in post-socialist countries when compared to Western Europe. The main objective of the present paper is to analyse the differences and similarities between Eastern and Western European countries with regard to one mobility programme – Erasmus+. The article presents the differences looking at macro data and quantitative questionnaire data.